Outcomes to first-line pembrolizumab in patients with PD-L1-high (≥50%) non–small cell lung cancer and a poor performance status. Issue 2 (4th August 2020) - Alessi, Joao V; Ricciuti, Biagio; Jiménez-Aguilar, Elizabeth; Hong, Fangxin; Wei, Zihan; Nishino, Mizuki; Plodkowski, Andrew J; Sawan, Peter; Luo, Jia; Rizvi, Hira; Carter, Brett W; Heymach, John V; et al.
Abstract : Background: Patients with non–small cell lung cancer (NSCLC) and a poor Eastern Cooperative Oncology Group Performance Status (ECOG PS) have been excluded from phase III immunotherapy clinical trials. We sought to evaluate clinical outcomes to first-line pembrolizumab in patients with advanced NSCLC, a PD-L1 Tumor Proportion Score (TPS) of ≥50%, and an ECOG PS of 2. Methods: We performed a multicenter retrospective analysis of patients with metastatic NSCLC and a PD-L1 TPS of ≥50% (negative for genomic alterations in EGFR and ALK ) who received treatment with first-line pembrolizumab. Clinical outcomes were compared in patients based on ECOG PS. Results: Among the 234 patients, 83.3% (n=195) had an ECOG PS of 0 or 1, and 16.7% (n=39) had an ECOG PS of 2. The baseline clinicopathological characteristics were balanced between the ECOG PS 0–1 vs 2 groups in terms of age, sex, tobacco use, histology, KRAS mutation status, presence of other potentially targetable driver mutations ( BRAF, MET, HER2, RET ), presence of brain metastases, and PD-L1 TPS distribution. Compared with patients with an ECOG PS of 0 or 1, patients with an ECOG PS of 2 had a significantly lower objective response rate (43.1% vs 25.6%; p=0.04), a numerically shorter median progression-free survival (6.6 months vs 4.0 months; HR 0.70 (95% CI 0.47 to 1.06); p=0.09), and a significantly shorter median overall survival (20.3 months vs 7.4 months; HR 0.42 (95% CI 0.26 to 0.68); p<0.001). On disease progression, patients with an ECOG PS of 2 were significantly less likely to receive second-line systemic therapy compared with patients with an ECOG PS of 0–1 (65% vs 22.2%, p=0.001). Conclusions: A subset of patients with NSCLC and an ECOG PS of 2 can respond to first-line pembrolizumab. However, clinical outcomes in this population are often poor and use of second-line systemic therapy is infrequent.